Case Study on Road Accidents in a Motorcycle-Propelled Public Transport - Maming, Jimmy Bernabe; Imbong, Maria Fe Planco (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The Philippines utilizes the motorcycle as informal transport services. Thus, the birth of the “habal-habal” motorcycle taxi that traverses not only in the secondary roads but also in the national highways. This case study intends to describe the experiences of the participants on the list of occurrences that ended in casualty and fatality and to identify problems in the policy implementations pertinent to road safety and management. This study utilizes interviews, observation, and data reviews in gathering the data while the Mayring (2002) approach was used in the data analysis procedure. Themes come out from the narratives of the participants like unlicensed driving involving minors, under-reporting of fatalities and non-use of safety gear during the flight. The output of the study is a proposed new Model on Malay Transportation Development and Management